The impact of Bruton’s tyrosine kinase inhibitor treatment on COVID-19 outcomes in Chinese patients with chronic lymphocytic leukemia - Yang, Shenmiao; Wei, Rong; Shi, Hongxia; Wang, Yazhe; Lai, Yueyun; Zhao, Xiaosu; Lu, Jin; Schmitz, Norbert (Frontiers in Oncology, 2024)
Background: Impact of B-cell depletion following treatment with Bruton tyrosine kinase-inhibitors (BTKi) on the outcome of SARS-Cov-2 infection in chronic lymphocytic leukemia (CLL) patients remain controversial. We investigated the impact of BTKi on susceptibility and the severity of COVID-19 in Chinese patients with CLL during the first wave of COVID-19 (Omicron variant). Methods: CLL patients (n=171) visiting the Institute of Hematology, Peoples ' Hospital, China (November 15, 2022-January 20, 2023) were included in the study. Seventeen patients receiving BTKi and venetoclax with or without obinutuzumab were excluded. Data from 117 patients receiving treatment with BTKi were collected using a standardized questionnaire through telephone interviews. Thirty-four patients without CLL-specific treatment served as controls. The data was analysed using IBM SPSS Software version 21 and a P value of <0.05 was considered statistically significant. Results: The median age of patients was 67 years and majority were males (n=100). Treatment with BTKi was not associated with higher incidence of COVID-19 (74% [95% Confidence Interval (CI) 60%, 92%]) versus 74% (CI 48%, 100%) without any treatment (P=0.92). Hypoxemia was reported by 45% (32%, 61%) and 16% (4%, 41%) (P=0.01). BTKi was the only independent risk factor of hypoxemia (Hazard Ratio [HR], 4.22 [1.32, 13.50]; P = 0.02). Five (5.7%) patients with COVID-19 under BTKi required ICU admission; 4 of them died. No ICU admissions/deaths were observed in the control group. Conclusion: In Chinese patients with CLL and treated with BTKi experienced more severe lung disease and ICU admissions due to COVID-19 than patients without CLL therapy. Frequency of infections with SARS-CoV-2, however, was not different in patients with or without BTKi treatment.